Human settlement in Polish territory during the Last Glacial Maximum (ca 24,000–19,000 cal. BP): the calm before a new deal - Połtowicz-Bobak, Marta; Bobak, Dariusz (Acta Geographica Lodziensia, 2020)
Human presence in Poland during the Late Pleniglacial is evidenced by Gravettian sites, mostly from Małopolska. Such settlement almost disappears from the archaeological record during the period between 24 and 19 ky cal. BP. Only a few sites from that period have been discovered – two workshops without absolute chronology, and some meagre records of settlement with uncertain dating to the LGM. The Polish territory was resettled in the19th and 16th millennium cal. BP onward, the settlers being associated with the Epi-Gravettian and Magdalenian cultures.